A hermeneutic of justice. Justice as discernment in Matthew - Huub Welzen (Acta Theologica)
In some important dictionaries for the study of the New Testament, ?????????? has two meanings: justice in the sense of distributive justice and righteousness as a relational notion. In Matthew, we discover that the word concerns a threefold loyalty: loyalty to the law, loyalty to fellow people, and loyalty to the will of God. In the Sermon of the Mount, the word is used in a polemical context. ?????????? is the congruency of the explanation of the law and doing the law. It is the opposite of ????????? which is the incongruence of explanation and doing. ?????????? is an eschatological reality. This means that it is a result of the coming of the kingdom of God in history. This coming is thought to occur at the end of time, but it is also a reality in the present. One can observe it at work in the conduct of people. It is a criterion in the discernment of the correct explanation of the law, and it is a criterion in the discernment of the correct doing.